The Effects of Service Excellence on Customer Satisfaction at Warung Tegal (Warteg) in Bekasi City - Pebriyanti, Mala; Tsardosslapito, Tsardosslapito; Supatrem, Supatrem; Chaerudin, Iman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Service excellence is a crucial element in the business sector, including Warung Tegal (Warteg) in Bekasi City, which faces intense competition in the culinary industry. Although many Wartegs offer affordable prices and varied menus, not all can provide satisfactory service. Shortcomings such as slow service, lack of staff friendliness, and inadequate cleanliness can affect customer satisfaction and loyalty. This study aims to measure the relationship and influence of service excellence quality on customer satisfaction at Warteg outets in Bekasi City. Focusing on aspects such as service speed, friendliness, cleanliness, menu variety, affordability, and location convenience, this research involved 100 respondents selected through incidental sampling techniques. Data were analyzed using linear regression tests, validity, reliability, normality, autocorrelation, and heteroscedasticity tests. The findings reveal that Service Excellence quality significantly impacts customer satisfaction, contributing 74.8% to its variance. The regression equation Y=5.492+1.060XY = 5.492 + 1.060XY=5.492+1.060X indicates that an improvement in service quality directly enhances customer satisfaction levels. This study provides practical insights for Warteg entrepreneurs to improve service quality, thereby boosting customer loyalty and competitiveness.